EXPRESSIVE SPEECH ACTS IN RESPONSES TO “TOT TOT WUK WUK” SIRENS - Satria, Yoga; Rika Ningsih (Universitas Muhammadiyah Makassar, 2026)
This study examines the use of language on social media as a means of expressing attitudes, emotions, and public evaluations of social phenomena. The focus of the research is on expressive speech acts found in the comment section of a Metro TV YouTube video titled “Fitra Eri Tanggapi Kendaraan Berstrobo Tot Tot Wuk Wuk.” The aim of this study is to describe the forms of expressive speech acts used by users in responding to the content. This research employs a qualitative approach with a content analysis method. The data consist of written utterances in the YouTube comment section that contain expressive speech acts. Data were collected through documentation techniques, including reading, recording, and identifying relevant comments. The data analysis was conducted by classifying the utterances based on types of expressive speech acts and interpreting their meanings within the context of digital communication. The results show that there are 50 instances of expressive speech acts, consisting of criticism (21 data), praise (17 data), expressions of gratitude (5 data), expressions of anger (4 data), condemnation (2 data), and congratulations (1 data). Meanwhile, forms such as apologizing and expressing condolences were not found. The dominance of critical expressions indicates that social media comment sections are often used as spaces to convey public evaluations of social issues.In conclusion, social media functions as a public communication space that enables individuals to express psychological attitudes, experiences, and perspectives on emerging social issues through various forms of expressive speech acts.